The effect of price and digital marketing on new balance shoe purchase decisions through consumer satisfaction as a mediation variable - Wardana, Aldipa Anogara; Saputro, Edy Purwo (Jurnal Mantik, 2026)
This study investigates how price and digital marketing influence New Balance shoe purchase decisions, with customer satisfaction serving as a mediating variable. Employing a quantitative approach grounded in positivist philosophy, data were collected via structured questionnaires from consumers who had previously purchased and used New Balance footwear. Responses were analyzed using SmartPLS, including tests for reliability, validity, regression, and mediation. Price was found to have a significant positive effect on both customer satisfaction and buying decisions, highlighting its central role in shaping consumer behavior. Digital marketing significantly enhanced satisfaction but did not exert a direct significant influence on purchase decisions. Customer satisfaction did not mediate the relationship between price or digital marketing and buying decisions, indicating that satisfaction alone does not guarantee actual purchases, which are also affected by trends, needs, and affordability. Overall, pricing emerged as the dominant factor influencing buying behavior, while digital marketing primarily reinforced perception and engagement. The study is limited by its focus on a single brand, a narrow set of variables, and reliance on online surveys. Practically, firms should maintain competitive pricing and optimize interactive marketing strategies, while future research could expand the range of variables and product categories